A systematic review and meta-analysis of the effectiveness and safety of COVID-19 vaccination in older adults - Xu, Kun; Wang, Zihan; Qin, Maorong; Gao, Yangyu; Luo, Na; Xie, Wanting; Zou, Yihan; Wang, Jie; Ma, Xingming (Frontiers in Immunology, 2023)
In the coronavirus disease 2019 (COVID-19) pandemic, vaccinations are essential for preventing COVID-19 infections and related mortality in older adults. The objectives of this study were to evaluate the effectiveness and safety of COVID-19 vaccines in in older adults. We systematically searched electronic bibliographic databases of PubMed, Web of science, Embase, Cochrane Library, Clinical trial.gov, Research Square, Open gray and Gray literature for studies published between January 1, 2020 and October 1, 2022. We retrieved 22 randomized controlled trials (RCTs) with a total of 3,404,696 old people (age over 60 years) were included in the meta-analysis. No significant publication bias was found. In the cumulative meta-analysis, we found that COVID-19 vaccines were effective in preventing SARS-CoV-2 infection (OR=0.38, 95%CI, 0.23-0.65, P=0.0004) and lowering COVID-19-related death (OR=0.16, 95%CI, 0.10-0.25, P<0.00001) for the elderly after vaccine. The antibodies seroconversion and geometric mean titers (GMT) levels significantly increased in the vaccinated older adults (OR=24.42, 95% CI, 19.29-30.92; SMD = 0.92, 95% CI, 0.64-1.20, respectively). Meanwhile, local and systemic adverse events rate after the COVID-19 vaccines administration were found in older adults (OR=2.57, 95%CI, 1.83-3.62, p＜0.00001). Although vaccination may induce certain adverse reactions to the elderly population, the available evidence showed that the COVID-19 vaccines are effective and tolerated in the decreasing of COVID-19-related death on older adults. It needs to abundantly plain to the elderly that the advantages of vaccination much outweigh any potential risks. Therefore, COVID-19 vaccination should be considered as the recommended strategy for the controlling of the COVID-19 disease by preventing SARS-CoV-2 infection and deaths on older adults. More RCTs are needed to increase the certainty of the evidence and to verify our conclusions.